World Cup 2014 – Professional Training Program for Brazilian Hotels - Assis, Silvone Alves; Pfitscher, Gerson Henrique; Abdalla, Humberto (International Journal of Advanced Corporate Learning (iJAC), 2011)
This paper presents an experience of implementing a professional training program for the Brazilian hospitality industry in the 12 cities that will be the headquarters of the World Cup in 2014. This project was developed in the context of the program â??Welcoming Cup